Low birth weight risk factors survey in neonates in Tehran - Tabatabaee, shima; Moradi, mohammad hasan (Advances in Nursing & Midwifery, 2011)
Abstract Background and aim Neonatal mortality rate is one of the main health problems which is affected by prenatal status, maternal, fetal and perinatal conditions. Low Birth weight (LBW) is one of the main causes of neonatal and infantile mortality & is one of the important problems in all of communities. The aim of this study is an evaluation of LBW causes in neonates born to mothers in teaching hospitals in Tehran. Materials and methods This case-control study was conducted to estimate LBW causes in born babies in Taleghani , Mahdieh & Hedayat hospitals, Tehran, Iran . Data such as birth weight, sex, maternal age, gestational age, birth interval, history of abortion, prenatal care, maternal occupation, level of education, systemic and underlying diseases, history of infections and smoking were extracted from medical records. Data were statistically analyzed by SPSS ver.15 using Chi-square,t-test and fisher exact test. Findings 7.7% of neonates were LBW newborns. Maternal age, gestational age, maternal weight and height, and the interval between births of LBW neonates were significantly lower compared with normal birth weight neonates. Multiple logistic regressions model was used to estimate the effects of most important predictors on low birth weight. The logistic model showed that the highest risks for low birth weight were related to low interval between 2 birth (OR=0.54, CI=0.32-0.91), Low maternal weight gain during pregnancy (OR=1.4, CI=0.73-2.061), maternal depression or Anxiety (OR=1.62, CI=1.21-2.805) –mother preeclampsia (OR=2.98, CI=2.09-4.32) preterm delivery (OR=3.95, CI=2.38-5.52). Conclusion The Results revealed that Low birth weight rates increases in the presence of short interval between two births,–mother preeclampsia, depression or anxiety, & preterm delivery. Keywords: LBW-LBW Risk factors, regression model